22nd International Conference and Exhibition on Electricity Distribution (CIRED 2013) 2013
DOI: 10.1049/cp.2013.0857
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of harmonic emission from the turbines through the collection grid to the public grid

Abstract: Abstract-This paper addresses the harmonic emission from a large off-shore wind farm. An overview is given of the issues, where a distinction is made between frequencies below and above 2 kHz. Three different approaches are presented: a simplified mathematical model; a more detailed mathematical model; and measurements and the point of connection for an off-shore wind farm. It is concluded from both models and measurements that the emission is small for frequencies above a few kHz. However, specific resonances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Power quality problems arise in large WPPs because of the harmonic emissions of WTs equipped with power electronics [1][2][3][4][5][6][7][8][9]. These harmonic emissions are amplified by parallel resonances in the collector grid if they are close to the resonance frequency [1,[6][7][8][9][10][11][12]. A summary of the most important WPP harmonic and resonance issues is presented in [6,8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Power quality problems arise in large WPPs because of the harmonic emissions of WTs equipped with power electronics [1][2][3][4][5][6][7][8][9]. These harmonic emissions are amplified by parallel resonances in the collector grid if they are close to the resonance frequency [1,[6][7][8][9][10][11][12]. A summary of the most important WPP harmonic and resonance issues is presented in [6,8,11].…”
Section: Introductionmentioning
confidence: 99%
“…• Although, in order to consider the influence of WT control on consumed harmonic currents, WTs are better characterized as Norton equivalent sources [7], the typical WT harmonic model as ideal current source is used in the study because it is commonly chosen to perform frequency scan studies and it offers a useful insight into parallel resonance analysis [1,8,[11][12][13][14]16]. However, further research is required to analyze the impact of WT control on this resonance.…”
Section: (B)mentioning
confidence: 99%
“…Most research works model converters as harmonic current sources and analyze the influence of WP parameters on parallel resonance [1,7,8,[11][12][13][14][15][16][17][18]. These studies are mainly based on frequency scan simulations which allow the frequency range and peak impedance values of parallel resonances to be established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relation between the emissions from individual turbines and from the park as a whole is discussed in a companion paper [3]. There it is concluded that the emission from a park can be higher as well as lower than the emission that would be obtained by adding the harmonic magnitudes of the individual turbine emissions.…”
Section: Propagation Through a Wind Parkmentioning
confidence: 99%